The Dual-specificity phosphatase Dusp15 is regulated by Sox10 and Myrf in Myelinating Oligodendrocytes - Muth, Katharina; Piefke, Sandra; Weider, Matthias; Sock, Elisabeth; Hermans-Borgmeyer, Irm; Wegner, Michael; Küspert, Melanie (Glia, 2016)
Differentiation of oligodendrocytes and myelin production in the vertebrate central nervous system require highly concerted changes in gene expression. The transcription factors Sox10 and Myrf are both central to this process and jointly regulate expression of myelin genes. Here we show that Sox10 and Myrf also cooperate in the activation of the gene coding for the dual specificity protein phosphatase Dusp15 (also known as VHY) during this process. Activation is mediated by the Dusp15 promoter, which is also sufficient to drive oligodendroglial gene expression in vivo. It contains both a functional Sox10 and a functional Myrf binding site. Whereas Sox10 binds as a monomer, Myrf binds as a trimer. Available data furthermore indicate that cooperative activation is not a function of facilitated binding, but occurs at a later step of the activation process. shRNA-mediated knockdown of Dusp15 reduced expression of early and late differentiation markers in CG4 and primary oligodendroglial cells, whereas Dusp15 overexpression increased it transiently. This argues that Dusp15 is not only a joint target of Sox10 and Myrf in oligodendrocytes but may also mediate some of their effects during oligodendrocyte differentiation and myelin formation. GLIA 2016;64:2120-2132.
EVALuna2:4997